Child Rights Law, Adoption Policy and Orphanage Management in Lagos:: Implications for Responsible Citizenship and the Actualization of the African Union 2063 Agenda - Amoo, Olajumoke (Journal of Contemporary International Relations and Diplomacy, 2022)
This paper examines the nexus between orphanage management in Child’s Rights and Adoption Policy in Lagos State, Nigeria, as a gauge of how much Nigeria strives to meet the African Union (AU) Agenda 2063. The research methodology includes sourcing informed views of resourceful scholars and workers on the subject matter; library search; relevant government documents, journal articles and conference proceedings. The findings of the study indicate that the situation of orphans and vulnerable children is escalating and beyond the capacities of many traditional families which necessitates institutional care and its role in an inclusive society for all children. The study is relevant in understanding the plight of orphans, vulnerable children and how States can support families and communities for improved developmental outcomes and as such produce wholesome individuals who will birth Africa’s renaissance.